Engineered anti-EGFRvIII targeted exosomes induce apoptosis in glioblastoma multiforme. (16th March 2023) - Rahmani, Rana; Kiani, Jafar; Tong, Wing Yin; Soleimani, Masoud; Voelcker, Nicolas H.; Arefian, Ehsan
Abstract: Background: The drug delivery for treatment of glioblastoma multiforme (GBM) has been unsatisfactory mainly due to the drug resistance and low targeting efficiency. The selective targeting of GBM cells and using a cocktail of therapeutic agents to synergistically induce apoptosis may help enhance the drug delivery. Methods: In this study, mesenchymal stem cells (MSCs) were engineered to produce exosomes, i.e. nanosized natural vesicles presenting anti-EGFRvIII (ab139) antibody on their surface while encapsulating two apoptosis-inducing gene therapy agents, i.e. cytosine deaminase (CDA) and miR-34a. Exosomes were characterised for their size, morphology, protein content and markers using dynamic light scattering and nanoparticle tracking analysis, cryo-TEM, Western blotting, respectively. miR-34a overexpression and Lamp2-ab139 protein expression were analysed using real-time PCR and flow cytometry, respectively. The armed exosomes were delivered to EGFRvIII positive GBM cells (U87EGFRvIII) as well as wild type cell line (U87), which was EGFRvIII negative. Apoptosis was quantified using flow cytometry in both EGFRvIII negative and positive U87 cells, receiving one gene therapy agent (either CDA or miR-34a) or a combination of them (CDAmiR). Results: Spherical shape exosomes with an average diameter of 110 nm and a membrane thickness of 6.5 nm were isolated from MSCs. Lamp2-ab139 was successfully expressed on the surface of transfected cells and their secreted exosomes. Induced apoptosis rates was significantly higher in U87EGFRvIII cells than for U87 cells, indicating selectivity. The cell death rate was 6%, 9% and 12% in U87, 13%, 21% and 40% in U87EGFRvIII cells for CDA, miR-34a and CDAmiR treatment respectively, showing a higher apoptosis rate in the cells receiving both drugs compared to when single therapy was applied. Conclusion: The experimental findings clearly show the improved apoptosis rate of GBM cells when treated by engineered exosomes armed with two gene therapy agents and targeted towards EGFRvIII antigen.